Dr. Susan Love's breast book - Love, Susan M.; Lindsey, Karen, 1944-; Love, Elizabeth (Journalist) (Hachette Go, an imprint of Hachette Books, 2023)
"While the amount of information regarding a breast cancer diagnosis is vaster than ever, online and off, what continues to be missing is the explanation behind the options. Most of the data online on medical sites is generic and often comes from the same source. Then there are the patient sites as well as many social media outlets that provide peer to peer support and information. This is important for emotional support but still leaves out the full range of options and the reasons for them. The Breast Book is where people go for a deeper understanding of how to make the best possible choices for their particular situations. Now in its seventh edition, the Breast Book has been fully revised to incorporate all the most recent developments in prevention, treatments and research"--